THE ROLE OF THE FAMILY IN CHARACTER EDUCATION FOR CHILDREN - Mustafa Habib; Dina Nadira (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
Family is not only a place where father, mother and children gather. A real family is more than that. Family is the most comfortable place for children. A happy family is like heaven on earth, as the words of the Prophet Muhammad SAW, that "My Home is My Heaven". Character formation cannot be carried out optimally by schools without cooperation from families. Family is the main and first education to shape the good and bad of the human person. The family plays a role in shaping the child's attitude and personality patterns. Children are likened to a blank sheet of white paper that must be filled in, in this case the role of parents is the one who is very dominant in educating children from an early age, with great tenderness and affection to build positive habits, capable of being an example. which is good and feeds halal & toyib. A religious atmosphere at home and at school will make it easier to form Emotional Intelligence (EQ) and Spiritual Intelligence (SQ) for children. And instilling character education from an early age is the most expensive price that parents need to pay for their children. Character is the main basis for othercharactereducation.